2010
DOI: 10.1111/j.1553-2712.2010.00948.x
|View full text |Cite
|
Sign up to set email alerts
|

Injury-adjusted Mortality of Patients Transported by Police Following Penetrating Trauma

Abstract: Background: More than a decade ago, the city of Philadelphia began allowing police transport of penetrating trauma patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
31
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 37 publications
3
31
2
Order By: Relevance
“…We previously described the relationship between mode of transport and outcomes in a single urban trauma center in which we found no overall mortality difference between groups and identified a trend toward decreased mortality for severely injured patients and patients with gunshot wounds who were transported by police. 22 The current study focuses on the population of an entire city, and although we still found no difference in mortality overall, we found decreased adjusted mortality in key subgroups.…”
Section: Discussioncontrasting
confidence: 63%
See 3 more Smart Citations
“…We previously described the relationship between mode of transport and outcomes in a single urban trauma center in which we found no overall mortality difference between groups and identified a trend toward decreased mortality for severely injured patients and patients with gunshot wounds who were transported by police. 22 The current study focuses on the population of an entire city, and although we still found no difference in mortality overall, we found decreased adjusted mortality in key subgroups.…”
Section: Discussioncontrasting
confidence: 63%
“…Patients included in a previously published single-center analysis were among those included in this population-based multicenter study. 22 Subjects who were transported by private vehicle or arrived to the emergency department (ED) by other means were excluded from the analysis because they were thought to represent a diverse and distinct subset of patients. 24 Subjects transferred into or out of trauma centers were excluded because initial transport or final outcomes could not be appropriately assessed.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In the several articles focused on evaluation of police hospital transport in Philadelphia and a few additional municipalities, the authors suggested that it is at least as effective as transport via EMS ambulances. It may, in fact, be life‐saving because of the greater presence of police vehicles on patrol and the often faster response times of law enforcement to shooting incidents (Band et al., ; Band et al., ; Branas et al., ; Wandling et al., ).…”
Section: Resultsmentioning
confidence: 99%